A REVIEW OF PEARL OYSTER (Pinctada maxima) CULTUREIN GENERAL - Ludi Parwadani Aji (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2011)
ABSTRACT                   Pearl oyster culture is unique because the product is gem not flesh and one of the species that produce pearl is Pinctada maxima (Silver or Gold lip pearl oyster). Stock for pearl oyster production can be collected from the wild or hatchery. However, hatchery production is a better solution to supply P.maxima for pearl production rather than just depend on wild stocks. Spat from the wild or hatchery will be grown-out for pearl production by longline or raft culture system method in ocean. Raft culture provide a work platform to repair, clean and store culture tools, while, longline culture has better design to deal with wave or wind exposure. There are identified different culture systems according different species (for example between P.maxima and P.fucata) and locations. Several constraints on P. maxima culture also identify such as biofouling organisms, predations and diseases that can reduce productivity and pearl quality. For example, mass mortalities of P.maxima occurred in Western Australia due to viral infection and it disrupted the pearl oyster industry. Therefore, several strategies are needed to mitigate those problems to achieve maximal productivity by using good management culture practice.       Key word: pearl oyster, P. maxima, management, culture